1990
DOI: 10.1038/bjc.1990.169
|View full text |Cite
|
Sign up to set email alerts
|

Ploidy as a prognostic indicator in end stage squamous cell carcinoma of the head and neck region treated with cisplatinum

Abstract: Summary We measured tumour cellular DNA in 102 patients entered into two phase III trials of chemotherapy for end stage squamous carcinoma of the head and neck. The median survival of untreated patients with aneuploid tumours was 55 days compared with 224 days for patients treated with cisplatinum. This difference was highly significant. In contrast the median survival of untreated patients with diploid tumours was 74 days compared with 118 days for treated patients. Although this difference is statistically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Using three murine tumour cell lines (KHT, SCCVII and B16F1O) they found that transient hypoxia enhanced the metastatic potential and that this was associated with the generation of a subpopulation of overreplicated cells. Although this association is not specific, it is consistent with the finding that abnormal cellular DNA content can be associated with a reduced life expectancy in a number of human cancers (Cornelisse et al, 1987;Zimmermann et al, 1987;Armitage et al, 1985;Fordham et al, 1986;Cooke et al, 1990). It can be argued that overreplicated cells may give rise to cells with amplified genes that code for metastasis-relevant products (Ling et al, 1985) since it has been shown that cells resistant to MTX or doxorubicin due to amplification to the genes coding for DHFR or p-glycoprotein respectively were derived from overreplicated cells (Rice et al, 1987).…”
supporting
confidence: 74%
“…Using three murine tumour cell lines (KHT, SCCVII and B16F1O) they found that transient hypoxia enhanced the metastatic potential and that this was associated with the generation of a subpopulation of overreplicated cells. Although this association is not specific, it is consistent with the finding that abnormal cellular DNA content can be associated with a reduced life expectancy in a number of human cancers (Cornelisse et al, 1987;Zimmermann et al, 1987;Armitage et al, 1985;Fordham et al, 1986;Cooke et al, 1990). It can be argued that overreplicated cells may give rise to cells with amplified genes that code for metastasis-relevant products (Ling et al, 1985) since it has been shown that cells resistant to MTX or doxorubicin due to amplification to the genes coding for DHFR or p-glycoprotein respectively were derived from overreplicated cells (Rice et al, 1987).…”
supporting
confidence: 74%
“…The potential doubling time of aneuploid tumours was significantly less than that of diploid tumours which may explain the observation that aneuploid tumours are often more responsive to therapy (Franzen et al, 1986;Barlogie et al, 1987;Guo et al, 1989). We have previously reported that in advanced unresectable squamous carcinoma of the head and neck there was a significant prolongation of survival in patients with aneuploid tumours compared with patients with diploid tumours when treated with cisplatin (Cooke et al, 1990). However a recent meta analysis of published data from six separate head and neck ploidy studies representing 1047 cases has cast doubt on the prognostic value of tumour DNA content in head and neck tumours other than in oral cancer (Stell, 1991).…”
Section: Discussionmentioning
confidence: 86%
“…In breast carcinoma diploidy has been reported to predict chemoresistance (17), but this is not a constant finding since in patients receiving adjuvant chemotherapy for breast carcinoma, DNA aneuploid tumors relapsed more frequently, suggesting a difference either in the natural history or in the chemosensitivity of the tumor (18). Head and neck tumors treated with cisplatin showed no correlation between their D N A content and their response to chemotherapy (19,20) but a clear survival benefit of chemotherapy was seen only in patients with aneuploid tumors (20). Sequential biopsies of oral carcinoma indicated better response to chemotherapy for diploid tumors and for tumors in which the initially aneuploid clone disappeared during treatment (21).…”
Section: Discussionmentioning
confidence: 99%